Dopamine and Cu+/2+ can induce oligomerization of α‐synuclein in the absence of oxygen: Two types of oligomerization mechanisms for α‐synuclein and related cell toxicity studies. Issue 3 (29th November 2013) - Ha, Yonghwang; Yang, Aerin; Lee, Seyoung; Kim, Kibong; Liew, Hyunjeong; Lee, Sang Hyung; Lee, Ju Eun; Lee, Hong‐In; Suh, Yoo‐Hun; Park, Hee‐Sung; Churchill, David G.
<x xml:space="preserve">Abstract</x> α‐Synuclein oligomers can induce neurotoxicity and are implicated in Parkinson's disease etiology and disease progression. Many studies have reported α‐synuclein oligomerization by dopamine (DA) and transition metal ions, but few studies provide insight into joint influences of DA and Cu2+. In this study, DA and Cu2+ were coadministered aerobically to measure α‐synuclein oligomerization under these conditions. In the presence of oxygen, DA induced α‐synuclein oligomerization in a dose‐dependent manner. Cu+/2+ did not effect oligomerization in such a manner in the presence of DA. By electrophoresis, Cu2+ was found easily to induce oligomerization with DA. This implies that oligomerization invoked by DA is reversible in the presence of Cu2+, which appears to be mediated by noncovalent bond interactions. In the absence of oxygen, DA induced less oligomerization of α‐synuclein, whereas DA/Cu2+ induced aerobic‐level amounts of oligomers, suggesting that DA/Cu2+ induces oligomerization independent of oxygen concentration. Radical species were detected through electron paramagnetic resonance (EPR) spectroscopic analysis arising from coincubation of DA/Cu2+ with α‐synuclein. Redox reactions induced by DA/Cu2+ were observed in multimer regions of α‐synuclein oligomers through NBT assay. Cellular toxicity results confirm that, for normal and hypoxic conditions, copper or DA/Cu2+ can induce cell death, which may arise from copper redox chemistry. From these results, we propose that DA and DA/Cu2+ induce different mechanisms of α‐synuclein oligomerization, cross‐linking with noncovalent (or reversible covalent) bonding vs. likely radical‐mediated covalent modification. © 2013 Wiley Periodicals, Inc.